Comprehensive and High‐Throughput Exploration of Chemical Space Using Broadband 19F NMR‐Based Screening. Issue 35 (22nd June 2020) - Lingel, Andreas; Vulpetti, Anna; Reinsperger, Tony; Proudfoot, Andrew; Denay, Regis; Frommlet, Alexandra; Henry, Christelle; Hommel, Ulrich; Gossert, Alvar D.; Luy, Burkhard; Frank, Andreas O.
Abstract: Fragment‐based lead discovery has become a fundamental approach to identify ligands that efficiently interact with disease‐relevant targets. Among the numerous screening techniques, fluorine‐detected NMR has gained popularity owing to its high sensitivity, robustness, and ease of use. To effectively explore chemical space, a universal NMR experiment, a rationally designed fragment library, and a sample composition optimized for a maximal number of compounds and minimal measurement time are required. Here, we introduce a comprehensive method that enabled the efficient assembly of a high‐quality and diverse library containing nearly 4000 fragments and screening for target‐specific binders within days. At the core of the approach is a novel broadband relaxation‐edited NMR experiment that covers the entire chemical shift range of drug‐like 19 F motifs in a single measurement. Our approach facilitates the identification of diverse binders and the fast ligandability assessment of new targets. Abstract : A new, universal 19 F broadband relaxation‐edited NMR experiment enables fast screening of the entire drug‐relevant fluorine chemical shift range for distinct hit molecules in a single measurement. It further facilitates the efficient generation and evaluation of large, chemically diverse compound libraries and expedites the ligandability assessment of any macromolecular target.